Cost Benefit Analysis: A Handbook (Book). - Merz, C. Mike; Burns, Thomas J. (The Accounting Review, 1980)
Abstract Reviews the book "Cost Benefit Analysis: A Handbook," by Peter G. Sassone and William A. Schaffer.